Performances Of Heat Tolerant Tomato (Solanum Lycopersicum) Hybrids During Rainy Season (Bangladesh Journal of Agricultural Research, 2011)
An investigation was undertaken with a view to observing the performance of newly developed summer tomato hybrids during May 2008 to September 2008 at experimental field of Horticulture Research Centre, BARI, Gazipur. Number of fruits per plant, individual fruit weight, fruit size, etc. was significantly higher when the plants were treated with hormone. Fruit yield per plant was quite high in the hormone treated plant (1.57 kg) compared to untreated plants (0.90 kg). In general, all the hybrids performed better when treated with hormone in respect of yield compared to their corresponding untreated plants. The hybrid WP7 × C- 51 had the highest individual fruit weight (56.0 g) Among the hybrids, HT019 × WP10 had the highest fruit yield per plant (1.87 kg) closely followed by C-11 × WP10 (1.81 kg) when the plants were treated with hormone. The untreated plants of the hybrid lines C-41 × WP8, HT019 × WP10 and C-41 × WP10 produced more than 1.0 kg of fruits per plant. This indicates that there is bright scope of tomato production during summer through with and without hormone application, though application of hormone had positive effect on tomato yield. Keywords: Heat tolerant tomato hybrids; rainy season. DOI: http://dx.doi.org/10.3329/bjar.v36i2.9243 BJAR 2011; 36(2): 189-196